Social demand and support for teacher professional development in Australia - Костіна, Людмила (Educational Dimension, 2015)
Kostina L. S. Social demand and support for teacher professional development in Australia. Social context of teacher professional development in Australian secondary schools is considered in the article. Main goals and directions of state support and demand for teacher professional learning are determined. The role and activities of Australian professional learning associations in teacher professional development is analyzed.